Exploring the Metabolic Implications of Dextrin and Maltodextrin on Type 2 Diabetes Mellitus and Insulin Resistance: Experimental Glycemic Risk Analysis (Part 2) - Hassan Darwish; Evan R Brewer; Lucas Nathaniel Mechling; Hagar M. Mohamed; Manohar Noone; Abir Ba Hajjaj; Una Gibbons; Hiba Al Lawati; Maimouna Al Mahrizi (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Spectrophotometric Analysis of Glycemic Risk from Dextrin and Maltodextrin: Implications for Type 2 Diabetes Mellitus and Insulin Resistance Aim: The growing global burden of Type 2 Diabetes Mellitus (T2DM) emphasizes the need for evaluating dietary components that influence glycemic control. Building on our previous systematic review (Part 1), this study expands the investigation through experimental spectrophotometric analysis, focusing on the quantification of dextrin and maltodextrin concentrations in commercial Stevia-based sweeteners and assessing their glycemic risk potential. Methods: Stevia sweetener solutions at four concentrations (100–400 mg/L) were analyzed using UV-Vis spectrophotometry at 580 nm following Lugol’s iodine staining. Calibration curves for dextrin and maltodextrin (50–500 mg/L) were constructed to estimate polysaccharide levels in the tested samples. Results: A dose-dependent increase in maltodextrin concentration was observed, ranging from 26.8 to 90.6 mg/L across the tested Stevia samples. Dextrin concentrations ranged from 9.9 to 35.9 mg/L. Higher sample concentrations correlated with elevated glycemic risk, with Stevia solutions at 300 mg/L and 400 mg/L demonstrating moderate to high potential for impacting blood glucose levels. Conclusion: The findings confirm that maltodextrin, even in products marketed as diabetic-friendly, may contribute to adverse glycemic responses in a concentration-dependent manner. Dextrin exhibited a comparatively safer metabolic profile. These results reinforce the importance of transparent food labeling and cautious dietary choices among individuals with or at risk for T2DM. This study serves as a direct continuation of our previously published systematic review (Part 1), bridging literature-based insights with experimental validation.
Keywords: Spectrophotometry; Type 2 Diabetes Mellitus; insulin resistance; maltodextrin; dextrin; Stevia; glycemic index